A systematic literature review exploring the nexus between circular economy and communities - Ceddia, Anna Rita; Oricchio, Stefano; Barberio, Grazia; Innella, Carolina (Frontiers in Sustainable Cities, 2024)
Circular Economy (CE) studies often focus primarily on technical and economic aspects of the transition process. Recently, some authors have started to enquire the social processes connected to of the CE, often referring to communities. This article provides a Systematic Literature Review on the nexus between CE and community to investigate its features according to the experiences reported in the collected documents. The retrieved corpus has been analyzed recurring to consolidated frameworks, as the R hierarchy, the societal areas challenges identified by the Strategic Research and Innovation Agenda developed by the EU project CICERONE, and to the spectrum of participation provided by the International Association for Public Participation. The participative dynamics found in the corpus are analyzed also considering the type of communities, tools, methodologies and goals reported in the retrieved documents. Besides descriptive statistics about the mentioned aspects, the article includes a discussion on some CE social aspects, problematizing and questioning the retrieved stakeholders engagement practices, recurring to a qualitatively selected literature. Conclusions address the main findings related to the most commonly found R strategy, community type, societal challenge areas and type of participative dynamics according to the analytical components chosen in the methodology. Research implications are illustrated, suggesting possible directions for future research to widen the analysis on the nexus between CE and communities.